What is the patient experience in advanced liver disease? A scoping review of the literature. Issue 5 (2nd July 2013) - Kimbell, Barbara; Murray, Scott A
Abstract : Background: There has been a dramatic increase in liver disease over recent decades, with morbidity and mortality rates predicted to rise significantly. In order to effectively support this growing patient population we need to understand the experiences, key issues and priorities of people living and dying with advanced liver disease. Aims: To establish what is currently known about the patient experience of advanced liver disease. Methods: Scoping literature review. We searched MedLine, Web of Science, CINAHL and PsychINFO databases. Eligibility criteria: original research and review papers written in English since 1990 relating to the adult patient experience of advanced liver disease. Papers focusing on treatment development, acute liver failure or post liver transplantation were excluded. Results: 240 abstracts were identified and 121 articles reviewed in full. Patients with advanced liver disease experience many physical and psychosocial challenges, often of a greater severity than those reported in other advanced conditions. They are affected by gastrointestinal problems and fatigue, with both linked to higher levels of depression. Socio-demographic variations in the patient experience occur. Only two studies explored the holistic patient experience. Conclusions: Our knowledge of the patient experience in advanced liver disease is mainly from quality of life instruments and quantitative research. There are methodological limitations in the existing research such that the holistic patient experience is not well described. Qualitative longitudinal research has great potential for contributing to our understanding of the complex needs and experiences of patients living with advanced liver disease.